Effects of topical anaesthetics and fluorescein on the real-time PCR used for the diagnosis of Herpesviruses and Acanthamoeba keratitis. Issue 11 (9th August 2006) - Goldschmidt, P; Rostane, H; Saint-Jean, C; Batellier, L; Alouch, C; Zito, E; Bourcier, T; Laroche, L; Chaumeil, C
Abstract : Background: The early microbiological diagnosis of corneal infections may prevent the condition from worsening. Aim: To study the potential interferences of oxybuprocain and fluorescein solutions used by ophthalmologists on the performances of the real-time polymerase chain reaction (PCR) carried out as routine test for diagnosis of keratitis. Methods: Quantified suspensions of Herpes simplex virus (HSV1), Varicella zoster virus (VZV), Cytomegalovirus (CMV) and Acanthamoeba with and without oxybuprocain or fluorescein added before DNA extraction were tested by real-time PCR. Results: The capacities of the real-time PCR to detect HSV, VZV, CMV and Acanthamoeba were reduced by oxybuprocain and fluorescein. Both products diluted to 1/16 reduced the PCR detection capacities for more than 2 logs (DNA copies/sample). Conclusions: The simultaneous introduction of fluorescein or topical anaesthetics into the tubes containing the specimens to be tested by PCR may lead to false negative results. Because corneal specimens for microbiological diagnosis of keratitis are obtained after topical administration of anaesthetics and corneal staining with fluorescein, ophthalmologists should be aware to rinse the eye surface intensively with appropriate eye solutions to minimise the risks of misdiagnosis.